RISK-ORIENTED CONTROL OF FISH PRESERVES - Кравченко, Ірина; Богатко, Надія; Бартків, Лариса; Тимошенко, Ольга; Коржов, Євген; Богатко, Альона; Гут, Тарас; Курмаш, Анна; Довбиш, Вікторія (SWorldJournal, 2023)
In Ukraine, various preserves are made from the fish of the special ambassador in accordance with the requirements of DSTU 19588:2009 according to the technological instructions in compliance with the State sanitary rules and regulations. Organoleptic, ph